2009
DOI: 10.1111/j.1742-4658.2008.06824.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the parasite inhibitor chagasin in complex with papain allows identification of structural requirements for broad reactivity and specificity determinants for target proteases

Abstract: Papain (EC 3.4.22.2) from the latex of the papaya fruit (Carica papaya) was one of the first known proteolytic enzymes, and its digestive properties were already being utilized in the 19th century. Detailed biochemical studies in the 20th century peaked with efforts in the 1960s, defining the chemistry of the enzymatic mechanism, delineating the concept of specificity for protein substrate recognition [1][2][3], and with elucidation of the A complex of chagasin, a protein inhibitor from Trypanosoma cruzi, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Three structural elements essentially responsible for the specific binding of cystatins to the active-site cleft of papain-like cysteine proteases are a conserved Gly at the N-terminus, a QxVxG motif situated in the β-hairpin loop between the second and the third strand, and an aromatic residue on the β-hairpin loop between the fourth and the fifth strand [13], [14], [15]. The parasite chagasins, cystatin-like proteins were newly found to have a similar recognition pattern with cysteine proteases [16], [17], [18], [19], [20]. Although chagasins strongly inhibit cysteine proteases, the three inhibitory loops of chagasins show low sequence homology to other cystatins.…”
Section: Introductionmentioning
confidence: 99%
“…Three structural elements essentially responsible for the specific binding of cystatins to the active-site cleft of papain-like cysteine proteases are a conserved Gly at the N-terminus, a QxVxG motif situated in the β-hairpin loop between the second and the third strand, and an aromatic residue on the β-hairpin loop between the fourth and the fifth strand [13], [14], [15]. The parasite chagasins, cystatin-like proteins were newly found to have a similar recognition pattern with cysteine proteases [16], [17], [18], [19], [20]. Although chagasins strongly inhibit cysteine proteases, the three inhibitory loops of chagasins show low sequence homology to other cystatins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has previously been demonstrated that Plasmodium parasites express a very potent chagasinlike cysteine protease inhibitor called falstatin, which has the capacity to block caspase activity [25]. This is very surprising since chagasin-like inhibitors are known to normally bind to conserved grooves of papain-like proteases [26,27] and caspases do not have such a groove [28].…”
Section: Completion Of Plasmodium Development In Hepatocytes Induces mentioning
confidence: 93%
“…In our docking model, the phenyl ring of EhICP2 Phe80 protrudes into the active site of papain. Redzynia and coworkers postulated that residue Thr31 of the chagasin BC loop is an "active-site-blocking residue", which interacts with the active site of papain (Redzynia et al, 2009), and also binds the catalytic cysteine of falcipain 2 by a water-assisted hydrogen bond (Wang et al, 2007). The corresponding residue in EhICP2 is Ser47.…”
Section: Molecular Docking Of Ehicp2 With Papainmentioning
confidence: 97%
“…To gain insights into the binding mechanisms of EhICP2 to a target protease, the structure of EhICP2 was superimposed onto the coordinates of chagasin from the papain-chagasin complex (Redzynia et al, 2009). To dock EhICP2 onto papain, we used the fiberdock program, which minimizes the EhICP2 molecule and favors ligand backbone flexibility as the determinant parameter in docking (Mashiach et al, 2010).…”
Section: Molecular Docking Of Ehicp2 With Papainmentioning
confidence: 99%
See 1 more Smart Citation